Asset Distribution, Inequality, and Growth - Deininger, Klaus (World Bank, Washington, DC, 2014)
With the recent resurgence of interest in equity, inequality, and growth, the possibility of a negative relationship between inequality and economic growth, has received renewed interest in the literature. Faced with the prospect that high levels of inequality may persist, and give rise to poverty traps, policymakers are paying more attention to the distributional implications of macroeconomic policies. Because high levels of inequality may hurt overall growth, policymakers are exploring measures to promote growth and equity at the same time. How the consequences of inequality are analyzed, along with the possible cures, depends partly on how inequality is measured. The authors use assets (land) rather than income - and a GMM estimator - to examine the robustness of the relationship between inequality and growth that has been observed in the cross-sectional literature, but has been drawn into question by recent studies using panel techniques. They find evidence that asset inequality - but not income inequality - has a relatively large negative impact on growth. They also find that a highly unequal distribution of assets reduces the effectiveness of educational interventions. This means that policymakers should be more concerned about households' access to assets, and to the opportunities associated with them, than about the distribution of income. Long-term growth might be improved by measures to prevent large jumps in asset inequality - possibly irreversible asset loss because of exogenous shocks - and by policies to facilitate asset accumulation by the poor.